MEWUJUDKAN WANITA SEHAT MELALUI PEKA : PROGRAM EDUKASI KEBERSIHAN WANITA - Kurniawan, Afif; Ramadhani, Dwi Yuniar; Syaiful, Yuanita (PPM STIKES Adi Husada, 2025)
Introduction & Aim One of the ways to protect yourself from viruses and bacteria is by maintaining personal hygiene. The problem of personal hygiene that sometimes women do not pay attention to is cleanliness in the feminine area. The feminine area is often in humid conditions. Hence, it becomes a breeding ground for viruses and fungi that can cause infections, one of which is vaginal discharge or flour albus. The purpose of this community service activity is to provide health education through the PEKA Program (Women's Hygiene Education Program) and the making of traditional drinks. Method of Activity: This activity was carried out in the RW 05 area of Kapasan Village, with a target of 22 women. The activity steps are preparing booklets, coordinating with residents, providing pre-test questionnaires followed by providing education, and post-tests and demonstrations of hand washing, correct ways of cebok, and making traditional drinks. Results: The results of Wilcoxon's statistical test on the knowledge of women of childbearing age were p= 0.00 while the attitude used the Paired Sample t-test statistical test, which was a value of p=0.00. Discussion: The increase in knowledge will make a person change behavior in a positive direction. Keywords: Women, Personal Hygiene, Education, Attitude